2015
DOI: 10.1098/rspb.2015.0927
|View full text |Cite
|
Sign up to set email alerts
|

Complex relationships between species niches and environmental heterogeneity affect species co-occurrence patterns in modelled and real communities

Abstract: ResearchCite this article: Bar-Massada A. 2015 Complex relationships between species niches and environmental heterogeneity affect species co-occurrence patterns in modelled and real communities. Proc. R. Soc. Species co-occurrence analysis is commonly used to assess how interspecific interactions dictate community assembly. Non-random co-occurrences, however, may also emerge from niche differences as well as environmental heterogeneity. The relationships between species co-occurrence patterns, environmental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 45 publications
1
55
0
Order By: Relevance
“…To that end, pairs of taxa were identified as potentially interacting if they were found more or less frequently together than expected by random chance. Given that every local environment is initially identical, cooccurrence patterns are not linked to initial abiotic conditions and "habitat-filtering," a common problem for studies done in situ (32). Overall, we observed a larger number of interactions in the anaerobic samples than in the aerobic samples (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 57%
“…To that end, pairs of taxa were identified as potentially interacting if they were found more or less frequently together than expected by random chance. Given that every local environment is initially identical, cooccurrence patterns are not linked to initial abiotic conditions and "habitat-filtering," a common problem for studies done in situ (32). Overall, we observed a larger number of interactions in the anaerobic samples than in the aerobic samples (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 57%
“…This study is unique as it explicitly examined several confounding factors that are often ignored (Bar‐Massada ), but may substantially bias the results of co‐occurrence analyses. For example, species co‐occurrence analyses typically conflate species interactions with environmental filtering, making separating the two difficult.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that non‐random species co‐occurrence patterns might emerge simply due to the degree of similarity in species’ niches, the amount of cohesion in their geographic distributions, and the environmental heterogeneity of the regions they inhabit (Connor, Collins & Simberloff ; Bar‐Massada ; Royan et al . ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations